Dispositional optimism and social networks: A systematic literature review - Amănălăchioaie Andreea; Diaconu-Gherasim Loredana R.; Curseu Petru L. (Psihologija, 2025)
This review advances the previous literature regarding how personality traits are related to the features of social networks by investigating how dispositional optimism is linked with the structure of personal social networks. We evaluated these relations from a socio-psychological perspective, suggesting that individual differences shape the structure of social networks people participate in as well as from a sociological perspective, arguing that the structural configuration of social networks shapes individual differences. A systematic literature review search was conducted in six databases (Science Direct, Scopus, Taylor and Francis, Sage Journals, Ingenta, and Pro-Quest) for articles published between 2000 and 2022. The results indicated that dispositional optimism is a relevant personality trait for structural indicators of social networks (i.e., size, contact frequency and social connection). Further, there is also some evidence that structural features of social networks predict dispositional optimism. Our review advances the previous literature by providing an integrative view on the way dispositional optimism is related to structural features of social networks.